Analysis of iron in-use stocks: Evidence from the provincial and municipal levels in China. (January 2023) - Yue, Qiang; Chai, Xicui; Zhao, Feng; He, Junhao; Li, Yun; Wang, Heming
Abstract: Rapid industrialization and urbanization in China have greatly promoted the use of steel throughout the country, making China the world's largest steel producer and consumer. Iron in-use stocks (IIUS) play an important role in the life cycle of steel products, and the study of IIUS is of great significance for the sustainable use of iron resources. There is limited information on the historical evolution of IIUS at the provincial and municipal levels in China. This study estimated and analyzed the spatial distributions of IIUS in Sichuan Province, Liaoning Province, Jiangsu Province, Hubei Province, Qinghai Province and Guangdong province from 2000 to 2018 using the bottom-up method. The research results show that the IIUS of Jiangsu was 462.9 million tons in 2018, and its per capita IIUS was 5.7 t/cap, which was the largest among the six provinces. The IIUS of Qinghai was 21.03 million tons in 2018, the lowest among the six provinces. The per capita IIUS in Sichuan was 2.7 t/cap in 2018, the lowest per capita level among the six provinces. From the perspective of industrial distribution, the construction industry is still the main carrier of IIUS. Based on the estimated results of IIUS, the spatial distributions at the municipal level were calculated. The distribution of IIUS density in each city was found to be unequal, and the level of economic development has a great impact on the IIUS density. The spatial distribution at the provincial and municipal levels can provide important and useful information for the efficient recycling of metal resources. Highlights: The iron in-use stocks (IIUS) at provincial level in China is calculated. The building industry still plays an important role in IIUS. The calculation of IIUS at the regional level is based on linear regression between IIUS, population and GDP etc. Large differences of IIUS indicate the importance of the selection of waste collection sites.